Mennonites, Amish, and the American Civil War - Lehman, James O. (Young Center books in Anabaptist & Pietist studies., 2007)
Explores the moral dilemmas faced by various religious sects and how these groups struggled to come to terms with the effects of wartime Americanization-- without sacrificing their religious beliefs and values.